Dashtakī (d. 1498) and Dawānī (d. 1502) on the Analysis of Existential Propositions - El-Rouayheb, Khaled (Oriens, 2019)
Abstract The present article is a reconstruction of a logical dispute concerning the analysis of existential propositions between the two rivals from Shiraz, Jalāl al-Dīn al-Dawānī (d. 1502) and Ṣadr al-Dīn al-Dashtakī (d. 1498), a dispute that continued to echo down to the nineteenth century, especially in Iran and the Indian subcontinent. The controversy was elicited by a passage from a discussion in the commentary by Qūshjī (d. 1474) on Ṭūsī’s Tajrīd in which Qūshjī had briefly suggested that perhaps the predicates “existent” (mawjūd) and “nonexistent” (maʿdūm) are unusual in not needing a copula to link them to the subject. Dashtakī thought that a copula is needed in both existential and non-existential predications, but that in existential predications the copula is simply the union of subject and predicate, whereas in non-existential predications there is an additional copula that signifies the existence or nonexistence of the predicate for the subject. Dawānī’s position was that existential and non-existential predications are exactly on a par and should both be analyzed into subject, copula and predicate.